SYNTHESIS, CHARACTERIZATION AND PHOTOPHYSICAL PROPERTIES OF EUROPIUM(III) PHTHALOCYANINES BEARING [4-(thiophen-3yl)-phenoxy] - Aytan Kilicarslan, Fatma; Erden, Ibrahim (YILDIZ TECHNICAL UNIV, 2017)
In this study, two novel phthalonitriles (1,4) and their corresponding metal-free (2,5) and Eu(III) phthalocyanine derivatives (3,6) bearing 4-(thiophen-3yl)-phenoxy groups were synthesized. These novel compounds were characterized by elemental analysis, FTIR, H NMR, UV-Vis, fluorescence, and mass spectroscopy. The aggregation behavior of these compounds was investigated in different solvents and concentrations. The effects of the substituent and the nature of the europium on the photophysical parameters are also reported.
Keywords: Phthalocyanine; fluorescence; aggregation; europium; PHOTOCHEMICAL PROPERTIES; LUTETIUM(III) PHTHALOCYANINE; MAGNETIC-PROPERTIES; DERIVATIVES; COMPLEXES; ZINC(II); DECKERS; Engineering